Untold Story : A Novel - Monica Ali (London Simon & Schuster, 2012)
Lydia, an Englishwoman abroad, chooses to escape her past. Although she builds a new life, forges friendships and makes a home, she cannot forget what she left behind: her children, her family and her heritage. But can she ever truly shake off her history ...?
Keywords: Celebrities -- Identity (Philosophical concept) -- Princesses